Green Disclosure Regulation: How Far has been Researched? - Rusydiana, Aam Slamet (Accounting and Sustainability, 2024)
This study aims to see the development of research on the topic of "Green Disclosure Regulation" and research plans that can be carried out based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Green Disclosure Regulation" which comes from the Dimension database with a total of 500 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the bibliometric map of "Green Disclosure Regulation" research development in the world. The results of the study found that there were 5 clusters with the most used words being regulation, disclosure, evidence, analysis, company, and environmental information disc. Then, the research path topics related to Green Disclosure Regulation are Effect of green disclosure regulation, Quality of corporate environmental disclosure, ESG rating on green innovation, Role of environmental regulation in finance, and Sustainability effects of green credit policy.